Pengaruh Facility Service Quality, Interactive Service Quality terhadaap Word of Mouth yang dimediasi oleh Satisfaction pada Nasabah Bank BCA di Tanggerang Kota - febianto, Iyan; Riorini, Vandayuli; khusosi, Akhmad (GEMA EKONOMI, 2023)
This study uses 3 variables consisting of One independent variable, namely word of mouth, one mediating variable, namely satisfaction and two independent variables, namely the quality of facility services and the quality of interactive services. Which aims to analyze the quality of service facilities, the quality of interactive services to word of mouth mediated by satiffaction. The sample used in this study was BCA bank customers in Tangerang City. Through a survey using a questionnaire with a total of 120 respondents and the method of data analysis in this study using the structural equation model (SAM) with AMOS version 23 software, the results of this study indicate that the variable quality of service facilities and quality of interactive services have a positive effect on satisfaction. However, it does not have a significant effect on word of mouth if you look at the role of satisfaction as a mediating role, which is sufficient to influence the quality of service facilities and the quality of interactive services on customer satisfaction at BCA Tangerang City bank. But these results add support and extend the findings of this article. These findings suggest that employee satisfaction fully mediates the relationship between facility service quality and interactive service quality, although we find a non-specific effect, the findings of this study account for the fact that the presence of bank customers who have fully service quality mediates the relationship between satisfaction and quality, which is in line with the model applied in actual research.